All of the accuracy in half of the time: Assessing abbreviated versions of the Test of Memory Malingering in the context of verbal and visual memory impairment. Issue 7 (3rd October 2022) - Cohen, Cari D.; Rhoads, Tasha; Keezer, Richard D.; Jennette, Kyle J.; Williams, Christopher P.; Hansen, Nicholas D.; Ovsiew, Gabriel P.; Resch, Zachary J.; Soble, Jason R.
Abstract: Objective The Test of Memory Malingering (TOMM) Trial 1 (T1) and errors on the first 10 items of T1 (T1-e10) were developed as briefer versions of the TOMM to minimize evaluation time and burden, although the effect of genuine memory impairment on these indices is not well established. This study examined whether increasing material-specific verbal and visual memory impairment affected T1 and T1-e10 performance and accuracy for detecting invalidity. Method: Data from 155 neuropsychiatric patients administered the TOMM, Rey Auditory Verbal Learning Test (RAVLT), and Brief Visuospatial Memory Test-Revised (BVMT-R) during outpatient evaluation were examined. Valid ( N  = 125) and invalid ( N  = 30) groups were established by four independent criterion performance validity tests. Verbal/visual memory impairment was classified as ≥37 T (normal memory); 30 T-36T (mild impairment); and ≤29 T (severe impairment). Results: Overall, T1 had outstanding accuracy, with 77% sensitivity/90% specificity. T1-e10 was less accurate but had excellent discriminability, with 60% sensitivity/87% specificity. T1 maintained excellent accuracy regardless of memory impairment severity, with 77% sensitivity/≥88% specificity and a relatively invariant cut-score even among those with severe verbal/visual memory impairment. T1-e10 had excellent classification accuracy among those with normal memory and mild impairment, but accuracy and sensitivity dropped with severe impairment and the optimal cut-score had to be increased to maintain adequate specificity. Conclusion: TOMM T1 is an effective performance validity test with strong psychometric properties regardless of material-specificity and severity of memory impairment. By contrast, T1-e10 functions relatively well in the context of mild memory impairment but has reduced discriminability with severe memory impairment.